Systems engineering of optimal control. Synthesis of the structure of the technological products conversion system (Part 1) - Lutsenko, Igor (Eastern-European Journal of Enterprise Technologies, 2014)
Study of current controlled systems and scientific publications has shown that the architecture of controlled systems, related to the products conversion is based on the principle of austerity and, in general, does not provide the possibility of implementing a full parametric optimization. The paper proposes to develop a controlled conversion system from highly specialized systems, each of which performs only one function. The conversion system has the ability of independent conversion process rate control, and finished products are transferred to the buffering system, which provides release of finished products with specified consumer properties and in the required volume to the consumption system. Herewith, the maximum number of degrees of freedom, which is a prerequisite for the implementation of the full parametric optimization is ensured. The product conversion system structure was synthesized based on the liquid portion heating system is synthesized. The system is presented in the form of interconnected simple mechanisms. It is experimentally found that systems with continuous feed - release of raw product are a special case of fully controllable systems with the architecture that provides the optimal control possibility. The developed models were tested and examined in specially designed free software constructor EFFLI. Link to the current model of the controlled system is available in the text.